Rapid Quantification and Validation of Biomarker Scopoletin in Paederia foetida by qNMR and UV–Vis for Herbal Preparation - Dai Chuan Tan; Alexandra Quek; Nur Kartinee Kassim; Intan Safinar Ismail; Joanna Jinling Lee (Molecules, 2020)
Scopoletin has previously been reported as a biomarker for the standardization of Paederia foetida twigs. This study is the first report on the determination and quantification of scopoletin using quantitative nuclear magnetic resonance (qNMR) in the different extracts of Paederia foetida twigs. The validated qNMR method showed a good linearity (r2 = 0.9999), limit of detection (LOD) (0.009 mg/mL), and quantification (LOQ) (0.029 mg/mL), together with high stability (relative standard deviation (RSD) = 0.022%), high precision (RSD < 1%), and good recovery (94.08–108.45%). The quantification results of scopoletin concentration in chloroform extract using qNMR and microplate ultraviolet-visible (UV-vis) spectrophotometer was almost comparable. Therefore, the qNMR method is deemed accurate and reliable for quality control of Paederia foetida and other medicinal plants without extensive sample preparation.